Analysis of the Impact of Tourism on Economic Growth of Gunung Kidul District - Catarina Wahyu Dyah; Endang Mulyani; Afriyanti Afriyanti; Hadi Cahyono (Universitas Muhammadiyah Ponorogo, 2022)
Tourism is one sector that affects economic growth. High economic growth is expected to provide a trickle-down effect on the development process in an area through the expansion of job opportunities, increasing the income level of the community so that it can ultimately reduce the poverty level. This research uses Mixed Method Research. The reason the researcher chooses this method is because using quantitative and qualitative approaches simultaneously (combined) can provide a better understanding of the research problem than being used separately. The results showed that tourist visits and the number of restaurants partially had no significant effect on the economic growth of Gunung Kidul Regency. This is influenced by the time series data used are still in the short term, the number of tourist objects partially has a positive and significant effect on economic growth in Gunung Kidul Regency.